1978
DOI: 10.1111/j.1476-5381.1978.tb08636.x
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Bradykinin and Oxytocin on the Isolated Whole Uterus and Myometrium of the Rat in Oestrus

Abstract: 1 A technique is described for obtaining a myometrial preparation devoid of endometrium, from the uterus of the rat in oestrus.2 Acetylcholine and prostaglandin F2a, (PGF2a) produced concentration-effect curves with the same maximal tensions and slope on the whole uterus and myometrial preparations. Concentration-effect curves to bradykinin and oxytocin on the myometrial preparation were altered, resulting in a shift to the right and a decreased maximum response compared with those produced by the whole uterus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Contractions produced by one or more of histamine, muscarinic agents, 5-hydroxytryptamine, and K' were slightly increased (either pD2 or E,,, or both) (Flavahan et al, 1985;Barnes et al, 1985;Hay et al, 1986a,b;Raeburn et al, 1986ab;Finnen et al, 1986;Holroyde, 1986), or reduced (this study, cf. Whalley, 1978), or were not affected by epithelium removal (Goldie et al, 1986;Raeburn et al, 1986a, Hay et al, 1986aThompson et al, 1986 and this study). Barnes et al (1985) found that indomethacin did not alter a slightly increased sensitivity to acetylcholine in bovine epithelium-denuded tracheae.…”
Section: Relaxant Agonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contractions produced by one or more of histamine, muscarinic agents, 5-hydroxytryptamine, and K' were slightly increased (either pD2 or E,,, or both) (Flavahan et al, 1985;Barnes et al, 1985;Hay et al, 1986a,b;Raeburn et al, 1986ab;Finnen et al, 1986;Holroyde, 1986), or reduced (this study, cf. Whalley, 1978), or were not affected by epithelium removal (Goldie et al, 1986;Raeburn et al, 1986a, Hay et al, 1986aThompson et al, 1986 and this study). Barnes et al (1985) found that indomethacin did not alter a slightly increased sensitivity to acetylcholine in bovine epithelium-denuded tracheae.…”
Section: Relaxant Agonistsmentioning
confidence: 99%
“…Despite removal of a large sheet of endometrial epithelial tissue, including a small part of the uterine smooth muscle, this latter tissue responded normally to acetylcholine and prostaglandin F2,. Effects of bradykinin and oxytocin were only slightly reduced in that their maxima were lower in endometriumdeprived preparations (Whalley, 1978). In 1979, Furchgott & Zawadski observed that the vascular endothelial lining was essential for relaxant effects of acetylcholine in vitro.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However the failure of the prostaglandin synthesis inhibitors to reduce contractions to Bk following serosal perfusion is consistent with the findings of Barabe et al (1977) who proposed that Bk had a direct action on longitudinal muscle strips from cat ileum, and segments of rat uterus. A similar dual action for Bk on the rat isolated uterus has been reported by Whalley (1978) who suggested that Bk has a direct action on the myometrium and an indirect action via release of PGLS from the endometrium.…”
mentioning
confidence: 71%
“…KNG1 is cleaved to release bradykinin, which is able to stimulate myometrial contractility [21] by stimulating IP3-dependent Ca 2+ release and the bradykinin B2 receptor is expressed in the myometrium at term [22]. Interestingly, the phosphorylation of KANK2 (SRC-1-interacting protein, SIP) by epidermal growth factor has recently been described in human myometrial cells [23].…”
Section: Discussionmentioning
confidence: 99%